Efeito residual da inclusão da raspa integral de mandioca em dietas secas ou úmidas no período de creche, sobre o desempenho posterior de suínos - Nogueira Junior, Francismá Gomes (2007)
Was used 32 castrated piglets of commercial lineage, weaned at 21 days old and approximately 6,0 kg live weight, with the objective of evaluating the effect of the inclusion of different levels of dried cassava root meal (0, 12, 24 and 36% of DCRM)and feed forms on the performance of piglets in the initial phase (21 to 70 days) and its residual effects on the phases of growth, termination, total period and the 90 kg slaughtering age. The experimental design used were randomized blocks in a factorial scheme 4 x 2 (four levels of inclusion of DCRM and two feed forms dried and wet diets) with four replications by treatment, being the experimental unit one animal. The criteria used for the block formation was the initial piglets weight. The daily average weight gain (DMWG), daily average fees intake (DMFI) and the feeds conversion (FC) weren’t affect significantly (P> 0,05) by inclusion of different levels of DCRM of dry or wet diets. It was concluded that independent of the feed forms of the integral cassava scrap can be used in rations for piglets in the day-care center phase until the level of 36% without compromising the zootecnic performance between the different phases and the 90 kg slaughtering age of live weight.